2023
DOI: 10.1186/s10033-023-00831-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Visualization of Grease Flow in a Gearbox

Abstract: Lubricating greases are widely used in e.g. open gear drives and gearboxes with difficult sealing conditions. The efficiency and heat balance of grease-lubricated gearboxes depend strongly on the lubrication mechanisms channeling and circulating, for which the grease flow is causal. The computational fluid dynamics opens up the possibility to visualize and understand the grease flow in gearboxes in more detail. In this study, a single-stage gearbox lubricated with an NLGI 1-2 grease was modeled by the finite-v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Therefore, it is possible to analyze the bearing wear and monitor the change of the bearing lubricant film thickness through the electric potential, which provides a new method for monitoring the bearing lubrication status. For visual analysis of grease flow, Liu et al [216] modeled and analyzed a greaselubricated gearbox utilizing the finite volume method to numerically study the fluid flow of grease. The simulation results show that when the gear rotates, there is only a localized effect on the bottom of the oil shell around the gear; when the grease filling level is low, there is a significant separation between the gear rotation and the grease; and when the grease fill level is high, there is a significant interaction between the gear and the grease, The lubrication status of the bearing directly reflects the health of the bearing; the scientific research and technical personnel and the industrial and commercial sectors have long been in the bearing lubrication status monitoring much research, but still need to be further improved and accurate.…”
Section: Analysis Of Wind Power Bearing Lubrication Research Based On...mentioning
confidence: 99%
“…Therefore, it is possible to analyze the bearing wear and monitor the change of the bearing lubricant film thickness through the electric potential, which provides a new method for monitoring the bearing lubrication status. For visual analysis of grease flow, Liu et al [216] modeled and analyzed a greaselubricated gearbox utilizing the finite volume method to numerically study the fluid flow of grease. The simulation results show that when the gear rotates, there is only a localized effect on the bottom of the oil shell around the gear; when the grease filling level is low, there is a significant separation between the gear rotation and the grease; and when the grease fill level is high, there is a significant interaction between the gear and the grease, The lubrication status of the bearing directly reflects the health of the bearing; the scientific research and technical personnel and the industrial and commercial sectors have long been in the bearing lubrication status monitoring much research, but still need to be further improved and accurate.…”
Section: Analysis Of Wind Power Bearing Lubrication Research Based On...mentioning
confidence: 99%
“…For planet gears, when the temperature is low, the power losses decrease with the temperature at a high rate. Liu et al [20,21,22] built an FZG gear test bed and established a 3D simulation model considering two-phase flow. By comparing the simulation results with the test results, it was found that they have good consistency.…”
Section: Introductionmentioning
confidence: 99%